PENGEMBANGAN MEDIA PAPAN PERMAINAN PANJAT PINANG - Desty Triastuti; Sa’dun Akbar; Edy Bambang Irawan (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2017)
Media is a very important component in the learning process. Media can be used as a toll for learning, that can be easy for the teachers to learn of the material, and at the same time can be facilitate the students to accepting and understanding of the material.  The purpose of this study is to produce the product that are specialized media to help the process of thematic learning. This media serves as a tool for stimulate memory recall and reinforce the material in students of fifth grade in elementary school. The media called board games panjat pinang has been validated on the the content and design, next then tried out on one to one evaluation, 6 students on small group evaluation and 23 students on field trial. The results of the tryouts indicating the level of feasibility of teaching materials is very high. The average validity is 90,025, attractiveness 91,80, effectiveness of 92,75, and practicality 92,18, so that media announced eligible and effective for use in thematic learning especially for matter circulatory systems human and animal. Media memiliki peranan yang sangat penting dalam proses pembelajaran. Media dapat dijadikan sebagai alat bantu belajar yang dapat memudahkan guru dalam penyampain materi sekaligus memudahkan siswa dalam menerima dan memahami materi.  Tujuan penelitian ini adalah menghasilkan produk media papan permainan panjat pinang untuk pembelajaran tematik. Media ini berfungsi sebagai alat bantu menstimulasi daya ingat dan penguatan materi bagi siswa kelas V SD. Media divalidasi pada aspek isi dan desain, diujicobakan kepada satu orang siswa pada uji coba perorangan, enam siswa pada uji coba kelompok kecil dan 23 siswa pada uji coba lapangan. Hasil uji coba menunjukkan tingkat kevalidan sangat tinggi. Rata-rata kevalidan 87,7, kepraktisan 90,55, kemenarikan 92,22, dan keefektifan 91,0. Berdasarkan skor perolehan tersebur, media dinyatakan layak dan efektif untuk digunakan di dalam pembelajaran tematik,  khususnya materi sistem peredaran darah manusia dan hewan.